2008
DOI: 10.1007/s00436-008-0951-2
|View full text |Cite
|
Sign up to set email alerts
|

Histological evidence for inoculative action of immature Linguatula serrata in lymph nodes of intermediate host

Abstract: The histopathological examination of 11 mesenteric lymph nodes from adult sheep infected with immature stages of Linguatula serrata revealed acute and chronic lesions with the presence of bacterial colonies and yeast cells. Bacteria were mainly present in acute, hemorrhagic, or necrotic lesions while yeast cells were seen mostly in the structure of chronic granulomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…These findings were consistent with the lesions reported by other investigators in sheep and camel (Miclãuş et al, 2008;Oryan et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…These findings were consistent with the lesions reported by other investigators in sheep and camel (Miclãuş et al, 2008;Oryan et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…The concurrent occurrence of visceral linguatulosis with paratuberculosis has been reported recently (Mir et al 2009). In addition, Miclãuş et al (2008) reported the presence of polymorphic bacteria, bacillar bacteria, or cocci in the vicinity of the Linguatula nymphs in the mesenteric lymph nodes, together with presence of the yeast cells within the central necrotic areas and between the infiltrated inflammatory cells in the infected adult sheep. The pathogenicity of Crohn's and tuberculosis diseases in humans is similar to paratuberculosis in livestock animals, and infection with the visceral linguatulosis may predispose to these or other diseases.…”
Section: Discussionmentioning
confidence: 96%
“…Follicular hyperplasia was also evident. Previous studies on the macroscopic appearance of nodes infected with parasitic nymphs have also reported enlarged lymph nodes with loose consistency and black discoloration as well as abscess formation, hemorrhagic and necrosis (Miclăuş et al, 2008;Sivakumar et al, 2005).…”
Section: Discussionmentioning
confidence: 87%